A genetic screen for Drosophila social isolation mutants and analysis of sex pistol - Mark Eddison (Nature Portfolio, 2021)
Abstract Prolonged periods of forced social isolation is detrimental to well-being, yet we know little about which genes regulate susceptibility to its effects. In the fruit fly, Drosophila melanogaster, social isolation induces stark changes in behavior including increased aggression, locomotor activity, and resistance to ethanol sedation. To identify genes regulating sensitivity to isolation, I screened a collection of sixteen hundred P-element insertion lines for mutants with abnormal levels of all three isolation-induced behaviors. The screen identified three mutants whose affected genes are likely central to regulating the effects of isolation in flies. One mutant, sex pistol (sxp), became extremely aggressive and resistant to ethanol sedation when socially isolated. sxp also had a high level of male–male courtship. The mutation in sxp reduced the expression of two minor isoforms of the actin regulator hts (adducin), as well as mildly reducing expression of CalpA, a calcium-dependent protease. As a consequence, sxp also had increased expression of the insulin-like peptide, dILP5. Analysis of the social behavior of sxp suggests that these minor hts isoforms function to limit isolation-induced aggression, while chronically high levels of dILP5 increase male–male courtship.